2013
DOI: 10.1115/1.4023703
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Response of the Herniated Human Abdomen to the Placement of Different Prostheses

Abstract: This paper describes a method designed to model the repaired herniated human abdomen just after surgery and examine its static mechanical response to the maximum intra-abdominal pressure provoked by a physiological movement (standing cough). The model is based on the real geometry of the human abdomen bearing a large incisional hernia with several anatomical structures differentiated by MRI. To analyze the outcome of hernia repair, the surgical procedure was simulated by modeling a prosthesis placed over the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…6). This observation corresponds to the results obtained experimentally by Anurov et al (2012) and numerically by Hernández-Gascón et al (2013), who investigated only two orientations of a surgical mesh in the central area of the abdominal wall. However, also a frequent solution of our optimisation scheme is 75 deg especially for hernia located in zone 4.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6). This observation corresponds to the results obtained experimentally by Anurov et al (2012) and numerically by Hernández-Gascón et al (2013), who investigated only two orientations of a surgical mesh in the central area of the abdominal wall. However, also a frequent solution of our optimisation scheme is 75 deg especially for hernia located in zone 4.…”
Section: Discussionsupporting
confidence: 90%
“…The principle that the properties of surgical meshes should match the properties of the abdominal wall and that implants should be oriented in the human body in accordance with the mechanics of the abdominal wall has been reported in the literature since 2001 (Junge et al, 2001). This issue was discussed e.g., by Kirilova et al (2012), Hernández-Gascón et al (2013), Anurov et al (2012). All these studies are limited to just one position of hernia orifice and two perpendicular orientations of implants.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that inappropriate positioning of anisotropic biomesh causes violation of endoprosthesis structure . The placement of an isotropic prosthesis reduce the influence on the mechanical behaviour . In this point of view, genipin is the most suitable agent for the cross‐linking DBP.…”
Section: Discussionmentioning
confidence: 99%
“…In another work, Hernández‐Gascón et al developed a numerical model of the repaired herniated abdomen based on an MRI solid model of the human abdomen with a large incisional hernia [Figure 7(a)]. They included different anatomical components, such as muscles and aponeuroses.…”
Section: Computational Modelingmentioning
confidence: 99%